Political Efficacy and Patterns of Online and Traditional Media Consumption among University Students - Sehrish Mushtaq; Fawad Baig; Muhammad Bin Suleman (Journal of Political Studies, 2018)
Online media has posed some serious threats to conventional media, as people are spending more time on it than traditional media. Online media has changed political and social attitudes of people. Different researches indicate positive effects of online media usage on political efficacy among students. This study aims to explore the difference in the level of political efficacy between the users of traditional and online media. A survey was conducted among 250 university students. Results show shift from traditional to online media among Pakistani students. It is found that university students have very little trust in the political system and its institutions, yet no statistically significant difference is found in political efficacy among the users of different media. There is no relationship between scores of political efficacy and frequency of Internet usage. Pakistani students seem to think about the political system independently of their media choices.